2012
DOI: 10.1152/ajpgi.00143.2011
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific regulation of ion transport by prolactin in rat colon epithelium

Abstract: The effect of prolactin (PRL) on ion transport across the rat colon epithelium was investigated using Ussing chamber technique. PRL (1 μg/ml) induced a sustained decrease in short-circuit current (I(sc)) in the distal colon with an EC(50) value of 100 ng/ml and increased I(sc) in the proximal colon with an EC(50) value of 49 ng/ml. In the distal colon, the PRL-induced decrease in I(sc) was not affected by Na(+) channel blocker amiloride or Cl(-) channel blockers, NPPB, DPC, or DIDS, added mucosally. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Although PRL is not originally found in the intestine, accumulating reports indicate that PRL is involved in a number of intestinal activities, such as modulating the calcium ion movement and altering the epithelial barrier integrity. 32 33 Our data indicate that PRL can also increase the production of IL-6 and IL-23 by DCs in the intestine. Others also found that PRL promoted the DC maturation and played a role in the pathogenesis of immune disorders, such as systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 65%
“…Although PRL is not originally found in the intestine, accumulating reports indicate that PRL is involved in a number of intestinal activities, such as modulating the calcium ion movement and altering the epithelial barrier integrity. 32 33 Our data indicate that PRL can also increase the production of IL-6 and IL-23 by DCs in the intestine. Others also found that PRL promoted the DC maturation and played a role in the pathogenesis of immune disorders, such as systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 65%
“…PRL and PRLR have been expressed along the gastrointestinal tract in fetal and neonatal stages during development (20). In adult rats, PRL induces active potassium-ion transport in distal colon and chloride-ion transport in proximal and transverse colon (21). IEC-6 colon crypt epithelial cells treated with PRL had increased expression of nutrient and mineral transport channel proteins, without inducing proliferation (22).…”
Section: Introductionmentioning
confidence: 99%
“…Ussing chambers have been used to study the uptake of glucose, heparin, oligonucleotides, antibiotics and amino acids (7,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The Ussing chamber is an ex vivo technique in which gut tissue is collected and mounted between two buffer-containing reservoirs (luminal and serosal chambers), thus permitting the study of the absorption of compounds across mounted tissues (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Studies On Materials Transport Across a Gastrointestinal Tra...mentioning
confidence: 99%